THE EFFECT OF INTERACTIVE LEARNING MEDIA ON STUDENTS’ LEARNING ACHIEVEMENT - Rindi Irma Audia (PT Rahis Cendekia Indonesia, 2026)
This study aimed to investigate the effect of interactive learning media on students’ learning achievement. The research employed a quantitative approach using an experimental design involving two groups: an experimental group and a control group. The participants of the study were 60 students selected through purposive sampling techniques, consisting of 30 students in the experimental group and 30 students in the control group. The experimental group was taught using interactive learning media, while the control group received instruction through conventional teaching methods. Data were collected through pre-tests and post-tests to measure students’ academic achievement before and after the treatment. The collected data were analyzed using descriptive statistics and an independent sample t-test. The results of the study revealed that students taught using interactive learning media achieved higher academic performance compared to those taught through traditional instructional methods. The average post-test score of the experimental group increased significantly after the implementation of interactive learning media. In addition, students in the experimental group demonstrated greater motivation, active participation, and better understanding of the learning materials during classroom activities. The statistical analysis showed that the significance value was lower than 0.05, indicating that interactive learning media had a significant positive effect on students’ learning achievement. The findings suggest that interactive learning media can create more engaging, effective, and student-centered learning environments. The use of multimedia elements such as animations, videos, and interactive activities helps students understand abstract concepts more easily and increases their interest in learning. Therefore, teachers and educational institutions are encouraged to integrate interactive learning media into classroom instruction to improve the quality of teaching and students’ academic outcomes.